21 Technologies for the 21st Century (Part 2 : the New Normal) - O'Reilly, Tim (O'Reilly Media, Inc., 2020)
Welcome to the new normal. In part two of his essay series, 21 Technologies for the 21st Century, Tim O'Reilly examines seven technologies that almost seem like "old news" but are now exploding into the mainstream. This is how change happens: "gradually then suddenly." Inspired by his essay "Welcome to the 21st Century," this four-part series explores 21 technologies that are reshaping the world. Each essay in this series focuses on skills that will increase your ability to respond to these impending changes. You'll also learn about resources on O'Reilly online learning that will help you acquire these skills. The complete essay series includes: Table Stakes -Fundamental skills that should be part of any robust strategy for dealing with changes that lie ahead The New Normal -Established technologies still in the early stage of adoption that are already accelerating into the mainstream The Future Is Knocking -Market opportunities that have the power to utterly transform our economy. What will be the next Silicon Valley? Wild Cards -Technology breakthroughs that could open up new opportunities that, at present, are just the stuff of science fiction Explore "The New Normal" and continue your journey into 21 technologies that will help all of us face this challenging and uncertain future